Community-Acquired Lung Abscess Caused by Legionella micdadei in a Myeloma Patient Receiving Thalidomide Treatment - Girard, Louis P. (American Society for Microbiology, 2007)
Legionella infection causes 2 to 14% of community-acquired pneumonia (CAP). Legionella micdadei constitutes <1% of these infections. We describe a case of cavitary L. micdadei CAP in a myeloma patient receiving thalidomide treatment. The importance of considering pneumonia and problems in diagnosing pneumonia caused by L. micdadei in this patient population are reviewed.